PREVALENSI GRADE SINGH INDEX PADA FRAKTUR PROXIMAL FEMUR PADA WANITA PASCA MENOPAUSE - Wijaya, Kezia Christina Viani; Suyasa, I Ketut; Wiratnaya, I Gede Eka; Astawa, Putu (E-Jurnal Medika Udayana; Vol 14 No 2 (2025): E-Jurnal Medika UdayanaDO - 10.24843/MU.2025.V14.i2.P07, 2025)
Proximal femur fractures, also known as pelvic fractures, are of increasing concern as they are associated with older age groups, particularly collum femur and intertrochanter femur fractures. This increase in fracture incidence is not only accompanied by increasing age, but also by decreasing bone mass associated with osteoporosis. The Singh index is a method that is thought to assess the degree of osteoporosis in the proximal femoral trabecular pattern. The purpose of this study was to determine the prevalence of Singh index grade in proximal femur fractures in postmenopausal women at Sanglah Central General Hospital, Denpasar in 2018-2020. This study is descriptive with a cross-sectional design. The sample consisted of 136 patients with proximal femur fractures in women over the age of 51 years who were then assessed for grade singh index. The research data were obtained from secondary data, namely patient medical record data in the period January 2018 to December 2020. The results showed that out of 136 samples, 55 patients (40.4%), consisting of 19 patients with collum femur fractures (42.2%) and 36 patients with intertrochanteric femur fractures (39.6%) experienced grade 3 singh index. The mean age of those with proximal femur fractures was 74.4 years. Keywords: Proximal Femur Fracture, Singh Index, Post-menopausal Women